An Opinion on Radio Time Signals - Sinzi, Akira M. (The International Hydrographic Review, 2015)
Due to the irregularity of the Earth’s speed of rotation, the rate of UT (*) (GMT) is not uniform. The unit of time by which frequencies are measured is formally defined as 1 atomic second. The current system of radio time signals in the UTC (**) scale is a result of compromise since it attempts to meet the requirements of users of UT as well as of frequencies. The rale of UTC is based strictly on the atomic time scale, and an instant expressed in UTC is an approximation of UT for various purposes in navigation and civil life. It is specified that the departure of UTC from UT shall normally be restricted to a maximum of 0.7 sec. In order to keep within this limit, one "leap" second can if necessary be introduced once or twice a year, preferably at the end of June and/or December. For navigation a departure of less than 1 sec between UTC and UT1 (***) can he tolerated in most cases. On the other hand, UTC, which is an approximation to UT, can scarcely be used in surveying, even if the disseminated coded correction DUT1 is applied. Moreover, in surveying UT is not required at the actual moment of observation. In 1973 the International Astronomical Union (IAU) adopted a recommendation that the current UTC system be amended to increase the maximum tolerance limit to 0.950 sec, with the possibility of introducing a leap second in March and/or September besides June and/or December. In a questionnaire on the UTC time signals about 50% of navigators responding supported a maximum limit for UT1 - UTC of less than 1 sec, 30% advocated larger values, and 20% would have preferred a smaller limit. Since the time system — which is at the very basis of all human activity — should be both simple and logical, I have considered it worthwhile to investigate the possibility of the introduction of International Atomic Time for all general uses in place of UTC.